1976
DOI: 10.3382/ps.0550070
|View full text |Cite
|
Sign up to set email alerts
|

Response to Selection for Hatchability in Turkeys at Three Altitudes

Abstract: Eggs from a commerical flock of Small White turkeys established at 76 meters above sea level were used to develop five lines of turkeys. Hatchability of fertile eggs was the only criterion used to establish selected lines at 76, 1524, and 2182 meters. Control lines were maintained at the 76 and 1524-meter locations. The objective of this study was to evaluate effects of the selection program on organ weights, body weight, and packed cell volumes (PCV). For two generations, eggs from one hatch at each of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Adrenal glands have not been considered in any of the currently available PBPK models for chickens. In turkeys, adrenal glands constitute 0.019% of body weight based on two studies (Davis & Siopes, 1985 ; Hobbs & Moreng, 1976 ) as shown in Table 4 . Davis and Siopes ( 1985 ) conducted a study to determine the effect of light duration on turkey poult performance and adrenal function, in which the adrenal weight values were measured in 97 turkeys.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adrenal glands have not been considered in any of the currently available PBPK models for chickens. In turkeys, adrenal glands constitute 0.019% of body weight based on two studies (Davis & Siopes, 1985 ; Hobbs & Moreng, 1976 ) as shown in Table 4 . Davis and Siopes ( 1985 ) conducted a study to determine the effect of light duration on turkey poult performance and adrenal function, in which the adrenal weight values were measured in 97 turkeys.…”
Section: Resultsmentioning
confidence: 99%
“…The pulmonary parenchyma compartment is commonly referred as the lung compartment in existing poultry PBPK models (Lautz et al., 2020 ; Yang et al., 2014 , 2015 ). Based on the data from eleven studies involving over 1,200 animal subjects (Adeyemi et al., 2008 ; Bowes & Julian, 1988 ; Buys, 1999 ; Cortright et al., 2009 ; Hobbs & Moreng, 1976 ; Marsden, 1940 ; Nestor et al., 2005 ; Tickle et al., 2014 ; Wideman, 1999 ; Wideman et al., 1996 ; Wolfenson et al., 1978 ), the mean relative weight of pulmonary parenchyma for broiler chickens of all ages, broiler chickens of market age, layers, and turkeys of all ages are approximately 0.71%, 0.61%, 0.66%, and 0.83% of the body weight, respectively (Tables 1 , 2 , 3 , 4 ). These values are comparatively higher than the weight used in the PBPK studies for chickens (Yang et al., 2014 , 2015 ), which was 0.54% of body weight experimentally derived from 10 chickens in Cortright et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations